2005
DOI: 10.1021/la0524418
|View full text |Cite
|
Sign up to set email alerts
|

More on the Phase Diagram of Laponite

Abstract: The phase diagram of a charged colloidal system (Laponite) has been investigated by dynamic light scattering in a previously unexplored range of salt and clay concentrations. Specifically the clay weight and salt molar concentrations have been varied in the ranges C w = 0.004 ÷ 0.025, C s = (1 × 10 −3 ÷ 5 × 10 −3 ) M respectively. As in the case of free salt water samples (C s ≃ 1 × 10 −4 M) an aging dynamics towards two different arrested phases is found in the whole examined C w and C s range. Moreover a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
146
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(160 citation statements)
references
References 23 publications
12
146
0
2
Order By: Relevance
“…Ten Brinke et al 90 found the sol-gel transition for hectorite was lower at $1.5 wt%. Mourchid et al [91][92][93][94] and other workers 22,95,96 found very similar state diagrams for Laponite RD, with the sol-repulsive gel transition at $0.5 wt%. In all these cases the gel transition occurs at a concentration at which the effective hydrodynamic volumes of the particles, extended by the range of the electrical double layer, begin to overlap.…”
Section: Sol-gel Transitionsmentioning
confidence: 66%
“…Ten Brinke et al 90 found the sol-gel transition for hectorite was lower at $1.5 wt%. Mourchid et al [91][92][93][94] and other workers 22,95,96 found very similar state diagrams for Laponite RD, with the sol-repulsive gel transition at $0.5 wt%. In all these cases the gel transition occurs at a concentration at which the effective hydrodynamic volumes of the particles, extended by the range of the electrical double layer, begin to overlap.…”
Section: Sol-gel Transitionsmentioning
confidence: 66%
“…%, and depending on the ionic strength, Laponite suspensions evolve from a low-viscosity liquid to various solid-like "arrested" states. The sol-gel transition in Laponite has been investigated mostly using light scattering [27,28,29,30,31]. The ageing properties of Laponite have triggered lots of effort and debate about the exact nature of these nonergodic states, in particular, about whether the material is actually a "gel" or a (Wigner) "glass" [30,32,33,34,35,36,37,38].…”
Section: Structure and Rheology Of Laponite Suspensionsmentioning
confidence: 99%
“…Numerous investigations have been addressed to define the state diagram of aqueous Laponite dispersions in the ionic strength vs clay concentration plane, i.e. to individuate the different regions of isotropic liquids, disordered (gels and glasses), ordered (nematic phases), flocculated states (Cummins, 2007;Gabriel, Sanchez, & Davidson, 1996;Jabbari-Farouji, Tanaka, Wegdam, & Bonn, 2008;Levitz, Lécolier, Mourchid, Delville, & Lyonnard, 2000;Mourchid, Lécolier, Van Damme, & Levitz, 1998;Mourchid, Delville, Lambard, Lécolier, & Levitz, 1995;Mongondry, Tassin, & Nicolai, 2005;Ruzicka, Zulian, & Ruocco, 2004;Ruzicka, Zulian, & Ruocco, 2006;Tanaka, Meunier, & Bonn, 2004;Tanaka, Jabbari-Farouji, Meunier, & Bonn, 2005). The various contradictions emerging from the comparison of the proposed Laponite dispersion state diagrams are partly apparent and can be mainly ascribed to different aging times and, secondarily, to different protocols of samples preparation or Laponite type .…”
Section: Introductionmentioning
confidence: 99%